Cost-Effectiveness of the CNIC-Polypill Strategy Compared With Separate Monocomponents in Secondary Prevention of Cardiovascular and Cerebrovascular Disease in Portugal: The MERCURY Study - Carlos Aguiar; Francisco Araujo; Gabriel Rubio-Mercade; David Carcedo; Silvia Paz; Jose María Castellano; Valentín Fuster (Journal of Health Economics and Outcomes Research)
**Background:** Cardiovascular (CV) diseases remain a leading and costly cause of death globally. Patients with previous CV events are at high risk of recurrence. Secondary prevention therapies improve CV risk factor control and reduce disease costs.